A Century of Clinical Use of Phages: A Literature Review - Kevin Diallo; Alain Dublanchet (MDPI AG, 2023)
Growing antibiotic resistance and the broken antibiotic market have renewed interest in the use of phages, a century-old therapy that fell into oblivion in the West after two decades of promising results. This literature review with a particular focus on French literature aims to complement current scientific databases with medical and non-medical publications on the clinical use of phages. While several cases of successful treatment with phages have been reported, prospective randomized clinical trials are needed to confirm the efficacy of this therapy.